Synthesis and Characterization of Hydroxyapatite from Crab Shell Waste (Scylla Serrata) Using the Precipitation Method - Nisa, Assholihatun; Dinda Putri Arnindi; Ni Ketut Sari (Jurnal Serambi Engineering, 2026)
The utilization of crab shell waste as a calcium source represents a value-added material development strategy while simultaneously reducing environmental pollution from fishery waste. This study aimed to synthesize hydroxyapatite (HAp) derived from crab shell waste via the precipitation method and to evaluate the effect of calcination temperature (800, 900, 1000, 1100, and 1200 °C) and Na₂HPO₄ concentration (0.75, 1.3, 1.85, 2.4, and 2.95 M) on the resulting material characteristics. The crab shells were initially calcined to obtain CaO as the calcium source, followed by reaction with Na₂HPO₄ solution as the phosphate precursor to form hydroxyapatite. The synthesized product was subsequently dried and calcined according to the designated temperature variations. Characterization was carried out using XRF, XRD, and SEM analyses. XRF results indicated the dominance of Ca and P elements with a Ca/P ratio approaching the stoichiometric value of hydroxyapatite (1.67). XRD patterns confirmed the formation of crystalline HAp phases, with increasing peak intensity and sharpness at higher calcination temperatures, indicating an enhanced degree of crystallinity. Variations in Na₂HPO₄ concentration influenced phase purity and the Ca/P ratio. SEM analysis revealed sub-spherical particle morphology with a tendency toward agglomeration at higher temperatures due to sintering effects. Overall, the findings demonstrate that controlling calcination temperature and phosphate precursor concentration plays a critical role in determining the composition, crystallinity, and morphology of hydroxyapatite synthesized from crab shell waste.